USING YOUTUBE VIDEO MATERIALS TO DEVELOP SPEAKING COMPETENCE - Kambarova Dildora Ibrokhimovna (Innovate Conferences, 2025)
In this article, the methodology of using audiovisual materials in the development of students’ speech competence, the methods of teaching grammar, inductive, deductive, interactive teaching methods, the advantages of using YouTube videos in classes, as well as, YouTube videos designed to improve students' speaking competence sites are listed. The method of using media, in particular, the Internet YouTube resource, in English language classes at higher education system is highlighted.
Keywords: speech competence, audiovisual materials, grammar teaching methods, inductive, deductive, interactive, YouTube video, lesson.